Attentional bias during emotional processing: evidence from an emotional flanker task using IAPS (2017)
Attention is biased towards threat-related stimuli. In three experiments, we investigated the mechanisms, processes, and time course of this processing bias. An emotional flanker task simultaneously presented affective or neutral pictures from the international affective picture system database either as central response-relevant stimuli or surrounding response-uninformative flankers. Participants’ response times to central stimuli was measured. The attentional bias was observed when stimuli were presented either for 1500 ms (Experiment 1) or 500 ms (Experiment 2). The threat-related attentional bias held regardless of the stimuli competing for attention even when presentation time was further reduced to 200 ms (Experiment 3). The results indicate that automatic and controlled mechanisms may interact to modulate the orientation of attention to threat. The data presented here shed new light on the mechanisms, processes, and time course of this long investigated by still largely unknown processing bias. © 2017 Informa UK Limited, trading as Taylor & Francis Group.